Circulating fibroblast activation protein α is reduced in acute ischemic stroke - Sieweke, Jan-Thorben; Grosse, Gerrit M.; Weissenborn, Karin; Derda, Anselm A.; Biber, Saskia; Bauersachs, Johann; Bavendiek, Udo; Tillmanns, Jochen (Frontiers in Cardiovascular Medicine, 2022)
Background Fibroblast activation protein α (FAP), a membrane glycoprotein with dipeptidyl-peptidase and collagenase properties, is expressed in atherosclerotic plaques and remodeling of the extracellular matrix based on fibrosis. Fibrosis is a main contributor of atrial cardiomyopathies. In acute MI, circulating FAP is associated with outcome. Here, we investigated the correlation of circulating FAP to echocardiographic parameters of atrial remodeling and neurological impairment in acute ischemic stroke. Methods Circulating FAP plasma concentrations were determined by ELISA in 47 patients with acute stroke and 22 control patients without stroke. Echocardiography was performed in all participants. Laboratory analysis, National Institutes of Health Stroke Scale (NIHSS) scoring and prolonged Holter-ECG-monitoring were performed in all stroke patients. Results Patients with acute stroke had lower circulating FAP concentrations than the control cohort (92 ± 24 vs. 106 ± 22 ng/mL, P < 0.001). There was no difference between the circulating FAP concentration comparing stroke due to atrial fibrillation, embolic stroke of undetermined source (ESUS) or atherosclerotic origin. Septal atrial conduction time (sPA-TDI) and left atrial (LA) volume index to tissue Doppler velocity (LAVI/a‘) representing echocardiographic parameters of LA remodeling did not correlate with FAP concentrations (sPA-TDI: r = 0.123, p = 0.31; LAVI/a‘: r = 0.183, p = 0.132). Stroke severity as assessed by NIHSS inversely correlated with circulating FAP (r = −0.318, p = 0.04). FAP concentration had a fair accuracy for identifying stroke in the receiver operating characteristic (ROC) analysis (AUC = 0.710, 95% CI: 0.577–0.843). A FAP concentration of 101 ng/mL discriminated between presence and absence of stroke with a sensitivity of 72% and a specificity of 77%. Lower circulating FAP concentration was associated with cardio-cerebro-vascular events within 12 months after admission. Conclusions Our study is the first to associate FAP with echocardiographic parameters of LA-remodeling and function. FAP did not correlate with sPA-TDI and LAVI/a‘. However, FAP was associated with stroke, neurological impairment, and cardio-cerebral events within 12 months. Therefore, FAP might enable individualized risk stratification in ischemic stroke.